Arsitektur Sistem Presensi Berbasis QR: Studi Kasus Bank bjb KCP Samsat Kota Bekasi - Purnama Magribi, Wahyu; Muhammad Fazly Qusyairy (Universitas Sains Indonesia Publishing, 2025)
The employee attendance system at Bank BJB KCP Samsat Kota Bekasi was previously done manually using paper attendance sheets, which had the potential to cause irregularities, lack of discipline, and errors in attendance records. To overcome these problems, this study aims to develop a computerized QR Code-based attendance information system using smartphones. This system is designed to simplify the attendance process, improve data accuracy, and minimize fraud in employee attendance recording. The system development utilizes Android Studio for the front end and a web-based design method with the CodeIgniter framework, MySQL database, and XAMPP server for the back end. Key features of the system include user login based on access levels, QR Code scanning for attendance, employee data management, manual attendance, attendance history, daily/monthly/annual report summaries, and report export to PDF format. The implementation results show that the system can replace manual processes with more efficient, faster, and well-documented procedures. System testing was conducted through alpha and beta testing, as well as black box testing, which confirmed that the system's functionality operates as expected. With this system in place, it is hoped that employee attendance processes will become more transparent, accountable, and supportive of improved discipline in the workplace.